Creation of MOFs with open metal sites by partial replacement of metal ions with different coordination numbers. Issue 8 (20th December 2018) - Harada, Yuki; Hijikata, Yuh; Kusaka, Shinpei; Hori, Akihiro; Ma, Yunsheng; Matsuda, Ryotaro
Abstract : Herein, we developed isostructural metal–organic frameworks (MOFs) [Cu1− x Pd x (SiF6 )(bpy)2 ] (bpy: 4, 4′-bipyridine) (SIFSIX-1-CuPd-3, -5 and -10) containing open metal sites using a partial metal-replacement approach. Abstract : Herein, we developed isostructural metal–organic frameworks (MOFs) [Cu1− x Pd x (SiF6 )(bpy)2 ] (bpy: 4, 4′-bipyridine) (SIFSIX-1-CuPd-3, -5 and -10) containing open metal sites using a partial metal-replacement approach. Starting from the SIFSIX-1-Cu-type MOF, some of the Cu 2+ ions having octahedral geometry were successfully replaced with Pd 2+ ions having square planar geometry in different ratios, while the framework structure was maintained. The results showed that gas adsorption properties of SIFSIX-1-Cu-type MOFs can be tuned via partial metal replacement.